The Existence and Relevance of Ahmadiyya Theology in Indonesia in the Perspective of Islamic Religious, Social, Political, and Education - Zidni Husein; Dimyati Sajari (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Indonesia is a country with a high level of religious diversity, making pluralism an inseparable social reality in societal life. Although Pancasila guarantees freedom of religion, differences in belief still have the potential to generate conflict, particularly when related to divergent theological interpretations within Islam. One group that frequently provokes debate is Ahmadiyya, whose presence has generated controversy in religious, social, political, and Islamic educational spheres. This study employs a descriptive qualitative approach using a library research method. Data were collected from scholarly books, journal articles, official government documents, religious fatwas, and relevant prior studies, and were analyzed through content analysis within a social constructionist paradigm. The study discusses the history of Ahmadiyya ’s arrival and development in Indonesia, the characteristics of Ahmadiyya theology and its relevance in religious, social, and political contexts, as well as Islamic education perspectives on Ahmadiyya theology. The findings indicate that Ahmadiyya entered Indonesia in the early twentieth century and expanded through missionary networks, yet faced widespread rejection due to theological differences, particularly regarding the concept of prophethood. In the socio-political context, Ahmadiyya is positioned as a minority group vulnerable to discrimination, while in Islamic education it is understood as an object of critical study aimed at strengthening creed while fostering moderation and tolerance. The conclusion emphasizes that although Ahmadiyya theology is rejected theologically, it remains relevant as a socio- religious phenomenon that should be understood critically and with civility.